INOVASI BASRENG IKAN GABUS (Channa striata) DENGAN PENAMBAHAN JAMUR TIRAM (Pleurotus ostreatus) - Aulia Fatihah Hidayat; Ita Fatkhur Romadhoni; Lilis Sulandari; Qorry’ Aina (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to determine the sensory characteristics of basreng snakehead fish (Channa striata) with the addition of oyster mushrooms (Pleurotus ostreatus) and determine the most preferred formulation. The study used a quantitative experimental method with the addition of oyster mushrooms at 10%, 20%, and 30%. Organoleptic tests on color, aroma, texture, taste, and preference were carried out by 35 panelists (30 semi-trained panelists and 5 trained panelists). Data were analyzed using the One-Way ANOVA test at a significance level of 5%. The results showed that the addition of oyster mushrooms significantly affected the color attribute, but did not significantly affect the attributes of aroma, texture, taste, and preference. The addition of 20% oyster mushrooms obtained an average color value of 4.43 (light brown but there are a few brown parts), aroma 3.89 (typical snakehead fish and oyster mushrooms are quite balanced), texture 3.86 (crunchy outer and inner textures, the surface is starting to become less even), taste 4.06 (quite balanced, but one of the flavors (snakehead fish or mushrooms) is slightly more pronounced), and preference 4.11 (like). Based on the results of the study, it can be concluded that the addition of 20% oyster mushrooms produces the best sensory characteristics. Keywords: basreng; snakehead fish; oyster mushrooms; sensory quality; organoleptic test